RECONSTRUCTING THE FOUNDATIONS OF VEDANTIC METAPHYSICS: A Pluriversal Model for Philosophizing - Neelamkavil, Raphael (Journal of Dharma, 2005)
This essay is concerned with a satisfactory method for ontological reconstruction and integration of Hindu thought, bearing in mind the theoretical lacunae that resulted in centuries of controversies on Nondualism, Dualism, Qualified Non-dualism, etc. For this purpose, I use here the bare minimum of fundamental ontological concepts that are commonly held by both the Upanisads and the different Vedantic Metaphysics like those of the major Upanisads and Sankara, Often I generalize them as Hindu Metaphysics from the point of view of the fundamentality of the theological principles I deal with, and for the sake of brevity, although the term is a partial misnomer for a highly variegated corpus of systems. I attempt to show what seems most fundamentally amiss in them and to point a way to bridge these lacunae.